School adjustment and suicidal ideation in adolescents enrolled in an educational institution in Puerto Colombia (2020)
Suicide and its attempts make up one of the relevant problems of current public health Objective: To describe the relationship between school adjustment and suicidal ideation in school adolescents. The main risk factors and protective factors in suicidal ideation were identified, and the relationship between variables was determined. Methodology: Descriptive correlational study, through stratified probabilistic sampling, 413 students from 6th to 11th grade were selected. The instruments evaluated suicidal ideation and school adjustment. Bayesian Inference and Machine Learning techniques were used in order to model the behavior of the different instruments. Octave was used as a computational support tool. Results: A negative correlation of school adjustment and suicidal ideation was found. Adolescents may develop a suicidal ideation as a consequence of the following factors: poor school performance 52 %, low academic expectations 27 %, and problems with school integration in 68 %. Conclusions: Adolescents with high levels of suicidal ideation may be related to low levels of school adjustment. The adolescent, feeling isolated, unable to establish friendship bonds between peers and poor school performance, will tend to look for negative exits or escapes such as suicidal ideation.